Development and validation of studetns' social interaction scale in practical physics class in Oyo state (2011)
The focus of this study was to develop and validate a scale that can be used by teachers to ascertain the type of interaction of students with their peers in practical physics class. The scale was administered to a sample of senior secondary school physics students (SS2) in twenty local government areas in Oyo State. The samples for this study were selected using multi stage random sampling method and 1000 students were selected. Four research questions posed guided the study and were answered using factor analysis method. To purify the data, factor loading of <0.3 were discarded and items with >0.40 loading on two or more factors were removed. The scale possessed reasonably high internal consistency and adequate construct validity. A principal component analysis was used to extract eight- factor solution which reflected what students considered before engaging themselves in social interaction with their peers. Confirmatory factor analysis was performed with maximum likelihood and x2 analyses. The eight factors extracted include student's socio-economics status, student's gender, student's residence, student's religious persuasion.